Apoptose, microinflamação e expressão de receptores de hidrocarboneto arílico nos folículos pilosos de pacientes com alopecia de padrão feminino - Ramos, Paulo Müller [UNESP] (2013)
Female pattern alopecia, or female androgenetic alopecia, is the main cause of hair loss in adult women and causes major impact on patient´s quality of life. It evolves from the progressive miniaturization of follicles that lead to a subsequent decrease of the hair density, leading to a non-scarring diffuse alopecia, with characteristic clinical, dermoscopic and histological pattern. Despite the high frequency and relevance about the psychological impact, its pathogenesis is not yet fully understood, but is influenced by genetic, hormonal and environmental factors. In addition, response to treatment is incostant. In this article, authors discuss the main clinical, epidemiological and physiopathological aspects of female pattern hair loss